DETRIMENTAL EFFECTS OF POLYMER STYRENE MALEIC ANHYDRIDE (SMA) ON CANINE SPERMATOZOA: A POTENTIAL FOR CONTRACEPTION IN MALE DOGS - MITHUN RAJ, PN; SRIDEVI, P; ARUNMOZHI, N; VIJAYARANI, K (The Indian Journal of Animal Reproduction, 2022)
The in vitro Interaction of positively charged polymer styrene maleic anhydride (SMA) with the negatively charged canine epididymal spermatozoa resulted in damage to acrosome and leaching out of enzymes. Moreover, the polymer reduced the pH of the environment to a level which was spermicidal. The damage to acrosome, mid piece and tail of canine spermatozoa brought about by addition of polymer SMA was evident by the Scanning Electron Microscopy and Atomic Force Microscopy studies. This study provides scope for development of a new contraceptive for male dogs.
Keywords: Atomic Force Microscopy; Canine contraception; Polymer; Scanning Electron Microscopy; SMA